1995
DOI: 10.1016/s0022-5347(01)67239-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Luteinizing Hormone-Releasing Hormone Agonist Leuprolide on Lipoproteins, Fibrinogen and Plasminogen Activator Inhibitor in Patients with Benign Prostatic Hyperplasia

Abstract: The impact of chronic administration of the luteinizing hormone-releasing hormone agonist leuprolide depot on cardiovascular risk factors was investigated in a controlled double-blind study comprising 50 evaluable patients with benign prostatic hyperplasia. In the 26 patients receiving leuprolide the mean total cholesterol level increased by 10.6%, high density lipoprotein cholesterol by 8.2% and triglycerides by 26.9% (p = 0.003, 0.052 and 0.050, respectively). Low density lipoprotein cholesterol levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…ADT has been associated with prothrombotic changes including increases in fibrinogen, plasminogen activator inhibitor 1, and tissue plasminogen activator antigen 4748 that may also explain a reported increase in venous thromboembolism. 49 Platelet counts are unaffected by ADT, 50 but platelet activation has yet to be characterized. In addition, this study did not include a placebo group because withholding ADT from men with prostate cancer and giving it to men without prostate cancer to enable a placebo group are both unethical because of the risks of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…ADT has been associated with prothrombotic changes including increases in fibrinogen, plasminogen activator inhibitor 1, and tissue plasminogen activator antigen 4748 that may also explain a reported increase in venous thromboembolism. 49 Platelet counts are unaffected by ADT, 50 but platelet activation has yet to be characterized. In addition, this study did not include a placebo group because withholding ADT from men with prostate cancer and giving it to men without prostate cancer to enable a placebo group are both unethical because of the risks of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in lipid profiles are highly variable during ADT use; however, many studies have reported increases in total cholesterol, triglycerides and HDL-C. 40,44,45 The increase in HDL-C observed while on ADT is a beneficial consequence, although it is unknown whether this improvement provides a cardio-protective effect. Regardless, increases in HDL-C are seen as early as 3-6 months within initiation of treatment.…”
Section: Mets and Androgen Deprivation Therapymentioning
confidence: 99%
“…Regardless, increases in HDL-C are seen as early as 3-6 months within initiation of treatment. 44,45 Due to the variability in lipid profile changes following ADT use, further investigation is warranted to determine the overall impact of ADT on cardio-metabolic risk in this population.…”
Section: Mets and Androgen Deprivation Therapymentioning
confidence: 99%
“…Hepatic insulin resistance is shown to be sufficient to produce dyslipidemia and increase the susceptibility to atherosclerosis in mice (50,51). In human clinical studies, GnRH agonists to suppress androgen/AR signaling cause increases in total cholesterol and triglycerides (52,53). It is therefore likely that functional deficiency of AR in the liver caused by GnRH agonists leads to these lipid alterations.…”
Section: Cell Type–specific Arko Mouse Modelsmentioning
confidence: 99%